Vulnerability and Resilience under Effects of Tsunamis: Case of Industrial Plants (2014)
The resilience approach represents a unified and integrated framework for the restoration process following disasters. Under given resilience parameters values, a resilient system is able to recover and be strengthened within a defined recovery period; otherwise, it is a non-resilient system. This paper considers different structures and focuses on several parameters which govern resilience together with their mechanical vulnerability under various hazards. A new method of theoretically measuring resilience, its link with mechanical vulnerability and its sensitivity analysis are investigated for industrial plants under the effects of flood and tsunami hazards: -Coastal industrial plants under the effects of a tsunami hazard: structural failure in tanks results from buoyancy (uplift), overturning, sliding by shear effect, excessive bending, or buckling. -Vulnerability and fragility curves are developed for various tanks of small and large sizes.